STING modulates HBV-related acute-on-chronic liver failure by mediating autophagy and macrophage polarization - Hao Zhang; Teng Liang; Wanlu Duan; Futing Liu; LiPing Li; Qian Liu; Jianfei Li; Qiyin Zong; Lei Jin; Qin Wang; Qiang Zhou (Immunobiology)
Background & Aims: HBV-related acute-on-chronic liver failure (HBV-ACLF) is a severe acute liver injury secondary to HBV-related chronic liver disease (with or without cirrhosis) and is characterized by a high short-term mortality rate. Presently, there is a paucity of experimental models that specifically focus on HBV-ACLF based on chronic hepatitis B. Therefore, this study aimed to establish an experimental mouse model of HBV-ACLF using chronic hepatitis B (CHB) as a basis and investigate the impact of STING activation on the disease. Methods: To simulate HBV-ACLF conditions, a model was constructed by combining chronic HBV replication (caudal vein high-pressure hydrodynamic injection of pAAV/HBV1.2 plasmid) and acute hepatic insult (intraperitoneal injection of Acetaminophen (APAP)). Then, model mice were administered either a STING agonist or STING inhibitor. Liver injury, STING pathway, autophagy flux, and macrophage polarization were assessed to elucidate the potential role of STING. Results: The mouse model developed chronic hepatitis B and acute liver injury, partially reflecting features of clinical HBV-ACLF based on CHB. STING activation, autophagy, and macrophage polarization were found to be involved in the disease process. During the early stage (6 h) of the STING agonist treatment group, the STING pathway was activated, autophagy flux was up-regulated, and liver inflammation and injury were alleviated. Contrastingly, at the late stage of STING agonist treatment (24 h, 48 h), macrophages were polarized to the M1 phenotype, exacerbating liver inflammatory infiltration and injury. However, treatment with a STING covalent inhibitor reversed these effects. Conclusions: Sting-induced autophagy exerts a protective effect on liver injury during the early stage. However, in later stages, STING may aggravate liver injury by shifting liver macrophage polarization to the M1 phenotype, thereby enhancing the inflammatory response.